Method for harmlessly treating lithium slag and preparing water-stable material from treated lithium slag
Through the crushing, calcining of lithium slag and the treatment of activated alumina, combined with the use of excitants, the resource waste and chemical stability of lithium slag in the water-stabilizing layer are solved, and the mechanical properties and resource utilization rate of the water-stabilizing layer are improved.
Patent Information
- Application Number
- CN202411295059.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-15
- Publication Date
- 2025-01-03
AI Technical Summary
The chemical substances remaining in the water-stabilizing layer material of lithium slag lead to waste of resources and chemical stability of materials. The existing preparation methods affect the amount of lithium slag and the performance of material.
By pulverizing lithium slag and calcining with sulfuric acid-containing materials, adding activated alumina-containing materials for chemical modification and filtration, adding exciter for grinding, obtaining detoxic lithium slag, and mixing it with cement, aggregate and curing agent to prepare water-stable Material.
Effectively reduce the roasting temperature of lithium slag, improve its hydration activity and resource utilization rate, reduce pollutant content, improve the chemical stability and corrosion resistance of the material, and improve the mechanical strength and drainage of the water-stabilizing layer. .
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of water-stable material preparation, and in particular to a method for harmlessly treating lithium slag and preparing water-stable material from the treated lithium slag. Background Art
[0002] Water-stabilizing layer is the abbreviation of cement-stabilized gravel layer, which is made of cement-consolidated graded gravel, compacted and maintained. The water-stabilizing layer has high strength, stiffness and stability. For asphalt pavement, the water-stabilizing layer is the main load-bearing layer of the entire road structure and an important structure to ensure the stability of the entire road structure. It can effectively transfer the vertical load of the road to the roadbed. As a semi-rigid material, cement-stabilized gravel is widely used in the base and subbase of my country's high-grade highways. The cement-stabilized gravel base has the characteristics of high strength, good plate properties, strong bearing capacity and strong anti-deformation ability. It is more suitable for my country's heavy-load traffic conditions. In addition, the source of cement-stabilized gravel base materials is wide, so the vast majority of my country's high-grade highway bases are cement-stabilized gravel materials. Therefore, the preparation of various water-stabilizing layer materials has become a hot research direction at home and abroad.
[0003] Lithium slag is waste residue produced in the process of extracting lithium and its compounds from spodumene and lepidolite, and its SiO2 and Al2O3 content reaches 70%. Due to the residual chemical substances, the stacking and landfilling of lithium slag threatens the surrounding environment and also causes waste of aluminosilicate mineral resources. The existing method generally directly uses lithium slag as a water-stabilizing layer material for preparation. This preparation method causes waste of residual aluminosilicate mineral resources in the lithium slag because the chemical substances of the lithium slag still remain in the water-stabilizing layer, and the harmful substances in the lithium slag may limit its dosage in the water-stabilizing material and affect the chemical stability of the material. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for harmlessly treating lithium slag and preparing water-stable materials from the treated lithium slag, aiming to solve the above technical problems.
[0005] To achieve the above object, the present invention provides a method for harmlessly treating lithium slag and preparing water-stable material from the treated lithium slag, comprising:
[0006] crushing the lithium slag;
[0007] Mixing the sulfuric acid-containing material with the crushed lithium slag to obtain a slurry mixture;
[0008] Calcination at 150-500°C for chemical modification to obtain calcined slag;
[0009] adding a material containing active alumina to the calcined slag to obtain a mixed material;
[0010] The mixed material is soaked in water and filtered to obtain leaching residue and leaching liquid;
[0011] Drying the leached residue, adding an activator and grinding the residue to obtain detoxified lithium residue;
[0012] The water-stabilizing material is prepared by mixing 4%-6% cement, 32%-36% detoxified lithium slag, 30-35% coarse aggregate, 20-24% fine aggregate, 1%-1.5% curing agent and 4-6% water based on dry weight according to the following mass parts.
[0013] In one embodiment, the lithium slag, the sulfuric acid-containing material, and the activated alumina-containing material are respectively 60% to 80%, 5% to 20%, and 10% to 25% in percentage.
[0014] In one embodiment, the sulfuric acid-containing material is concentrated sulfuric acid with a mass fraction of at least 70%.
[0015] In one embodiment, the active alumina-containing material is aluminum hydroxide or calcined kaolin.
[0016] In one embodiment, the activator includes 12%-25% gypsum, 14%-18% quicklime, 10%-15% water glass and 6%-13% sodium carbonate, and the amount of the activator added is 0.1% to 0.5% of the lithium slag.
[0017] In one embodiment, the specific surface area of the detoxified lithium slag after grinding is 550m 2 / kg~700m 2 / kg.
[0018] In one embodiment, the coarse aggregate is crushed stone or steel slag coarse aggregate.
[0019] In one embodiment, the fine aggregate is natural sand or artificial sand.
[0020] In one embodiment, the curing agent includes 20%-30% sodium silicate, 20%-30% phosphogypsum, 15%-20% calcium chloride, and 15%-20% magnesium oxide.
[0021] In one embodiment, the water content of the lithium slag is 0-25%.
[0022] In the technical solution of the present invention, the method for harmlessly treating lithium slag and preparing water-stable material from the treated lithium slag comprises:
[0023] crushing the lithium slag;
[0024] Mixing the sulfuric acid-containing material with the crushed lithium slag to obtain a slurry mixture;
[0025] Calcination at 150-500°C for chemical modification to obtain calcined slag;
[0026] adding a material containing active alumina to the calcined slag to obtain a mixed material;
[0027] The mixed material is soaked in water and filtered to obtain leaching residue and leaching liquid;
[0028] Drying the leached residue, adding an activator and grinding the residue to obtain detoxified lithium residue;
[0029] The water-stabilizing material is prepared by mixing 4%-6% cement, 32%-36% detoxified lithium slag, 30-35% coarse aggregate, 20-24% fine aggregate, 1%-1.5% curing agent and 4-6% water based on dry weight according to the following mass parts.
[0030] The present application performs harmless treatment on lithium slag by adding materials containing active alumina, thereby improving the problems of low hydration activity, high alkali content and large fluctuation of composition of lithium slag. More gel structures are generated through activators, thereby realizing resource utilization, high performance and harmless utilization of lithium slag.
[0031] By mixing sulfuric acid-containing materials with lithium slag through solid-liquid homogeneous reaction, the roasting temperature is effectively reduced, and efficient leaching and detoxification of valuable elements are achieved. Materials containing activated alumina can selectively adsorb specific harmful components and reduce the content of pollutants in lithium slag. At the same time, the treatment process is simplified, the environmental impact is reduced, and the resource utilization of lithium slag is improved.
[0032] By mixing lithium slag with materials containing activated alumina, the original alumina in the lithium slag is further activated, and the porosity of the activated alumina helps to improve the pore structure of the lithium slag, thereby improving its drainage and air permeability in the water-stabilizing layer, and further improving the chemical stability and corrosion resistance of the water-stabilizing material.
[0033] While effectively improving the quality of the water-stabilizing layer, lithium slag resources are effectively utilized, which improves resource utilization. Combined with activators and curing agents, the mechanical strength and corrosion resistance of the water-stabilizing layer concrete can be effectively improved. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.
[0036] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0037] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0038] The invention provides a method for harmlessly treating lithium slag and preparing a water-stable material from the treated lithium slag.
[0039] The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag provided by the embodiment of the present invention includes:
[0040] crushing the lithium slag;
[0041] Mixing the sulfuric acid-containing material with the crushed lithium slag to obtain a slurry mixture;
[0042] Calcination at 150-500°C for chemical modification to obtain calcined slag;
[0043] adding a material containing active alumina to the calcined slag to obtain a mixed material;
[0044] The mixed material is soaked in water and filtered to obtain leaching residue and leaching liquid;
[0045] Drying the leached residue, adding an activator and grinding the residue to obtain detoxified lithium residue;
[0046] The water-stabilizing material is prepared by mixing 4%-6% cement, 32%-36% detoxified lithium slag, 30-35% coarse aggregate, 20-24% fine aggregate, 1%-1.5% curing agent and 4-6% water based on dry weight according to the following mass parts.
[0047] In the present application, lithium slag is harmlessly treated by adding materials containing active alumina to improve the problems of low hydration activity, high alkali content and large fluctuation of composition of lithium slag. More gel structures are generated by activators to realize resource utilization, high performance and harmless utilization of lithium slag.
[0048] By mixing sulfuric acid-containing materials with lithium slag through solid-liquid homogeneous reaction, the roasting temperature is effectively reduced, and high-efficiency leaching and detoxification of valuable elements are achieved. Materials containing activated alumina can selectively adsorb specific harmful components. Under certain pH conditions, activated alumina can adsorb beryllium ions through ion exchange or surface complexation, and can also produce hydroxyl radicals and induce thallium oxidation precipitation, thereby achieving the removal of beryllium and thallium, while reducing soluble harmful substances such as chloride ions. Reduce the content of pollutants in lithium slag, simplify the treatment process, reduce environmental impact, and improve the resource utilization of lithium slag.
[0049] By mixing lithium slag with materials containing activated alumina, the original alumina in the lithium slag is further activated. The activated alumina and the alumina in the lithium slag will form a composite adsorbent with a synergistic effect. This composite material will show better adsorption performance and selectivity than the individual components. In addition, the addition of activated alumina can improve the dispersibility of alumina in lithium slag, reduce particle agglomeration, and thus improve adsorption efficiency. The porosity of activated alumina helps to improve the pore structure of lithium slag, thereby improving its drainage and air permeability in the water-stabilizing layer, and further improving the chemical stability and corrosion resistance of the water-stabilizing material.
[0050] While effectively improving the quality of the water-stabilizing layer, lithium slag resources are effectively utilized, which improves resource utilization. Combined with activators and curing agents, the mechanical strength and corrosion resistance of the water-stabilizing layer concrete can be effectively improved.
[0051] The lithium slag, the sulfuric acid-containing material, and the activated alumina-containing material are 60% to 80%, 5% to 20%, and 10% to 25% respectively in percentage.
[0052] Wherein, the water content of the lithium slag is 0-25%;
[0053] Wherein, the sulfuric acid-containing material is sulfuric acid, which is concentrated sulfuric acid with a mass fraction greater than or equal to 70%;
[0054] Wherein, the activated alumina includes aluminum hydroxide, calcined kaolin, etc.;
[0055] The activator is compounded from 12%-25% gypsum, 14%-18% quicklime, 10%-15% water glass, and 6%-13% sodium carbonate, and the amount of the activator added is 0.01%-0.05% of the lithium slag, and the amount of the activator added is 0.1%-0.5% of the lithium slag;
[0056] The grinding method is ball milling or vertical milling, and the lithium slag is ground to a specific surface area of 550m 2 / kg~700m 2 / kg.
[0057] The present application adopts the above-mentioned compound activator, which can provide an alkaline environment for hydration, generate more gel structures, and improve the density and mechanical properties of the water-stable material.
[0058] In addition, the cement is ordinary Portland cement. The coarse aggregate can be crushed stone or steel slag coarse aggregate, and the fine aggregate refers to natural sand or artificial sand with a smaller particle size;
[0059] The curing agent is composed of 20%-30% sodium silicate, 20%-30% phosphogypsum, 15%-20% calcium chloride and 15%-20% magnesium oxide.
[0060] The present application is explained below through specific embodiments.
[0061] Comparative Example
[0062] 80 parts of crushed lithium slag and 10 parts of 70% sulfuric acid are mixed evenly, and then put into a kiln for roasting at 300 degrees. 10 parts of aluminum hydroxide are added to the roasted slag and mixed evenly. The slag is sent to a pulping tank and water is added for pulping. After the prepared slurry is fully stirred, it is sent to a filter press to filter the water to obtain a detoxified lithium slag, which is marked as L-1.
[0063] Take 30 parts of sodium silicate, 30 parts of phosphogypsum, 10 parts of calcium chloride and 30 parts of magnesium oxide and stir them thoroughly to obtain a curing agent.
[0064] Take 32 parts of L-1 detoxified lithium slag, 6 parts of cement, 35 parts of coarse aggregate, 23 parts of fine aggregate, 1 part of curing agent and 5 parts of water, and put them into a water-stabilizing material mixer and mix them evenly to obtain water-stabilizing material.
[0065] The unconfined strength of the water-stabilized material after molding and hardening for 7 days is 6.6MPa.
[0066] Embodiment 1
[0067] 80 parts of crushed lithium slag and 15 parts of 70% sulfuric acid were mixed evenly and put into a kiln for roasting at 300 degrees. 10 parts of aluminum hydroxide were added to the roasted slag and mixed evenly. The slurry was sent to a pulping tank and water was added for pulping. After the prepared slurry was fully stirred, it was sent to a filter press to filter the water, and 0.4 parts of an activator was added and ground for 17 minutes to obtain a detoxified lithium slag, which was marked as L-2.
[0068] Take 25 parts of sodium silicate, 30 parts of phosphogypsum, 10 parts of calcium chloride and 35 parts of magnesium oxide and stir them thoroughly to obtain a curing agent.
[0069] Take 32 parts of L-2 detoxified lithium slag, 6 parts of cement, 35 parts of coarse aggregate, 23 parts of fine aggregate, 1 part of curing agent and 5 parts of water, send them into a water-stabilizing material mixer and mix them evenly to obtain water-stabilizing material.
[0070] The unconfined strength of the water-stabilized material after 7 days of molding and hardening is 7.2MPa.
[0071] Embodiment 2
[0072] 80 parts of crushed lithium slag and 15 parts of 70% sulfuric acid were mixed evenly, and then put into a kiln for roasting at 400 degrees. 10 parts of aluminum hydroxide were added to the roasted slag and mixed evenly. The slurry was sent to a pulping tank and water was added for pulping. After the prepared slurry was fully stirred, it was sent to a filter press to filter the water, and 0.4 parts of an activator was added and then ground for 20 minutes to obtain a detoxified lithium slag, which was marked as L-3.
[0073] Take 20 parts of sodium silicate, 35 parts of phosphogypsum, 15 parts of calcium chloride and 30 parts of magnesium oxide and stir them thoroughly to obtain a curing agent.
[0074] Take 32 parts of L-3 detoxified lithium slag, 6 parts of cement, 35 parts of coarse aggregate, 23 parts of fine aggregate, 1 part of curing agent and 5 parts of water, send them into a water-stabilizing material mixer and mix them evenly to obtain water-stabilizing material.
[0075] The unconfined strength of the water-stabilized material after 7 days of molding and hardening is 7.3MPa.
[0076] Embodiment 3
[0077] 80 parts of crushed lithium slag and 15 parts of 70% sulfuric acid were mixed evenly and put into a kiln for roasting at 400 degrees. 20 parts of aluminum hydroxide were added to the roasted slag and mixed evenly. The slurry was sent to a pulping tank and water was added for pulping. After the prepared slurry was fully stirred, it was sent to a filter press to filter the water, and 0.4 parts of an activator was added and then ground for 20 minutes to obtain a detoxified lithium slag, which was marked as L-4.
[0078] Take 30 parts of sodium silicate, 30 parts of phosphogypsum, 10 parts of calcium chloride and 30 parts of magnesium oxide and stir them thoroughly to obtain a curing agent.
[0079] Take 32 parts of L-4 detoxified lithium slag, 6 parts of cement, 35 parts of coarse aggregate, 23 parts of fine aggregate, 1 part of curing agent and 5 parts of water, send them into a water-stabilizing material mixer and mix them evenly to obtain water-stabilizing material.
[0080] The unconfined strength of the water-stabilized material after molding and hardening for 7 days is 7.6MPa.
[0081]
[0082] Table 1
[0083] In summary, this application effectively utilizes lithium slag resources and improves resource utilization while effectively improving the quality of the water-stabilizing layer. In combination with activators and curing agents, it can effectively improve the mechanical strength and corrosion resistance of the water-stabilizing layer concrete.
[0084] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for harmlessly treating lithium slag and preparing water-stable materials from the treated lithium slag, characterized in that: The method for harmlessly treating lithium slag and preparing water-stable material from the treated lithium slag comprises: crushing the lithium slag; Mixing the sulfuric acid-containing material with the crushed lithium slag to obtain a slurry mixture; Calcination at 150-500°C for chemical modification to obtain calcined slag; adding a material containing active alumina to the calcined slag to obtain a mixed material; The mixed material is soaked in water and filtered to obtain leaching residue and leaching liquid; Drying the leached residue, adding an activator and grinding the residue to obtain detoxified lithium residue; The water-stabilizing material is prepared by mixing 4%-6% cement, 32%-36% detoxified lithium slag, 30-35% coarse aggregate, 20-24% fine aggregate, 1%-1.5% curing agent and 4-6% water based on dry weight according to the following mass parts.
2. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The lithium slag, the sulfuric acid-containing material, and the active alumina-containing material are respectively 60% to 80%, 5% to 20%, and 10% to 25% in percentage.
3. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The sulfuric acid-containing material is concentrated sulfuric acid with a mass fraction of at least 70%.
4. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The active alumina-containing material is aluminum hydroxide or calcined kaolin.
5. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The activator comprises 12%-25% of gypsum, 14%-18% of quicklime, 10%-15% of water glass and 6%-13% of sodium carbonate, and the added amount of the activator is 0.1%-0.5% of the lithium slag.
6. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The specific surface area of the detoxified lithium slag after grinding is 550m 2 / kg~700m 2 / kg.
7. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The coarse aggregate is crushed stone or steel slag coarse aggregate.
8. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The fine aggregate is natural sand or artificial sand.
9. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim 1, characterized in that: The curing agent comprises 20%-30% of sodium silicate, 20%-30% of phosphogypsum, 15%-20% of calcium chloride and 15%-20% of magnesium oxide.
10. The method for harmless treatment of lithium slag and preparation of water-stable material from the treated lithium slag according to claim, characterized in that: The water content of the lithium slag is 0-25%.
Citation Information
Cited By
Equipment and method for preparing lepidolite slag planting substrate for agricultural cultivation
CN120240278A
Equipment and method for preparing lithium mica slag planting substrate for agricultural cultivation
CN120240278B
Method for efficiently removing beryllium and thallium in lithium slag
CN120864543A
Method for efficiently removing beryllium and thallium in lithium residue
CN120864543B
A method for solidifying heavy metal ions of lithium slag
CN121342540B